Effect of Beam Size on Shear Strength of Reinforced Concrete Normal Beams - Nasir Ghadhban, Hadi (Journal of Engineering and Sustainable Development, 2007)
This paper studies the shear capacity of normal strength concrete (NSC) reinforced beams with and without web reinforcement, as indicated by available research and explain the effect of beam size on shear strength of reinforced concrete beams. Two equations are proposed for design which is simple to use, safe and have low coefficient of variation (COV) when used for NSC.The results of analysis for NSC indicate that the proposed equations are conservative and give lower COV and smaller range of results when compared with the available methods of design which are based on the ACI.318M-02 [1], Canadian [2], B.S.8110-97 [3], New Zealand [4] codes and one equation proposed by Zsutty [5].By applying regression analysis was applied to both types of beams, with and without web reinforcement, two design shear equations are proposed, one for each type of beam.The computer programs which are used for this purpose are (QBASIC, Graph Win, and SPSS).